Bullying di Lingkungan Sekolah Dasar dalam Perspektif Pendidikan Karakter - Muhammad Nawir; Asri Pratiwi; Anniswah Firdaus; Nevianti; Femilianita; Hikmawati T; Nasrullah; Nurul Rofika (STKIP Subang, 2026)
Bullying in elementary school environments is a serious problem that affects students’ psychological, social, and academic development. Bullying behaviors such as teasing, exclusion, threats, and physical violence are still frequently found, indicating weak internalization of character values from an early age. This study aims to describe the forms of bullying that occur in elementary schools, analyze the contributing factors, and examine the role of character education in preventing and addressing bullying. The research employed a descriptive qualitative approach with elementary school students and teachers as the research subjects. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results showed that bullying in elementary schools appears in verbal, physical, and social forms, influenced by peer environment, parenting patterns, and the lack of reinforcement of character values in schools. The implementation of character education emphasizing empathy, responsibility, tolerance, and mutual respect was proven to reduce bullying tendencies and increase students’ awareness in building positive social interactions. Therefore, character education plays a strategic role as both a preventive and curative approach in creating a safe, comfortable, and character-based elementary school environment.